Ice amplifies ligand-controlled mineral dissolution in microscale hot spots - Tao Chen; Tao Luo; Tra My Bui Thi; Hervé Colloc; Claire Roiland; Laurent Le Pollès; Khalil Hanna; Jean-François Boily (Proceedings of the National Academy of Sciences, 2026)
Cold-region ecosystems are highly sensitive to climate change, yet the geochemical processes shaping their future remain poorly understood. Here, we show that ice systematically enhances mineral dissolution through freeze concentration into microscale reactive hot spots. Using goethite nanoparticles as a model iron oxide and environmentally relevant inorganic anions common in soils, waters, and aerosols (chloride, fluoride, sulfate), we demonstrate that ligand-promoted dissolution rates under mildly acidic conditions scale with binding affinity in both ice and liquid water, with ice enhancing rates across all reactive ligands. Fluoride, the strongest complexing agent, increased dissolution more than fourfold in ice, while weakly binding perchlorate produced no measurable dissolution in either phase. Reactions persisted well below the eutectic temperature, mediated by minute volumes of liquid-like water stabilized within networks of micron-sized mineral aggregates. Our findings highlight ice as a dynamic medium driving iron release, with implications for nutrient availability, carbon cycling, and biogeochemical feedbacks in rapidly warming polar and alpine regions.